Reliability and failure of electronic materials and devices - Ohring, Milton, 1936- (Academic Press is an imprint of Elsevier, 2014)
"Reliability and Failure of Electronic Materials and Devices is a well-established and well-regarded reference work offering unique, single-source coverage of most major topics related to the performance and failure of materials used in electronic devices and electronics packaging. With a focus on statistically predicting failure and product yields, this book can help the design engineer, manufacturing engineer, and quality control engineer all better understand the common mechanisms that lead to electronics materials failures, including dielectric breakdown, hot-electron effects, and radiation damage. This new edition adds cutting-edge knowledge gained both in research labs and on the manufacturing floor, with new sections on plastics and other new packaging materials, new testing procedures, and new coverage of MEMS devices"-- Provided by publisher.
Includes index.
Machine generated contents note: CH 1 An Overview of Electronic Devices and Their Reliability CH 2 Electronic Devices: Materials Properties Determine How They Operate and Are Fabricated CH 3 Defects, Contamination and Yield CH 4 The Mathematics of Failure and Reliability CH 5 Mass Transport-Induced Failure Ch 6 Electronic Charge-Induced Damage CH 7 Environmental Damage to Electronic Products CH 8 Packaging Materials, Processes, and Stresses CH 9 Degradation of Contacts and Packages CH 10 Degradation and Failure of Electro-Optical and Magnetic Materials and Devices CH 11 Characterization and Failure Analysis of Material, Devices and Packages CH 12 Future Directions and Reliability Issues.
Keywords: Electronic apparatus and appliances -- Reliability.; System failures (Engineering); elektronické knihy; electronic books